THE IMPORTANCE OF THE CLINICAL BIOCHEMISTRY SECTOR IN COVID-19: LITERATURE REVIEW (Editora Impacto Científico, 2025)
The COVID-19 pandemic, caused by SARS-CoV-2, has brought unprecedented challenges to global public health and highlighted the importance of the Clinical Biochemistry sector. This study, based on a narrative literature review, aims to highlight the relevance of this area in the diagnosis, monitoring, and prognosis of the disease. The gold standard method for viral detection was RT-PCR, which proved to be highly sensitive and specific, while serological and rapid tests, despite their limitations, played a complementary role in epidemiological studies and mass screening. In addition to diagnostic methods, the evaluation of biochemical and hematological biomarkers was fundamental to understanding the clinical evolution of COVID-19. Changes such as increased C-reactive protein (CRP), ferritin, procalcitonin, LDH, liver enzymes, creatinine, and D-dimer, in addition to reduced albumin, showed a strong correlation with disease severity and adverse clinical outcomes. These markers allowed for risk stratification, therapeutic monitoring, and early identification of complications. It is concluded that Clinical Biochemistry played an indispensable role in tackling the pandemic, providing essential data for clinical management and understanding the pathophysiology of COVID-19. Furthermore, its relevance is reaffirmed not only in current emergencies but also as a strategic component in preparing for future global health crises.